Pengaruh Electronic Word Of Mouth (E-Wom) Dan Brand Image Terhadap Purchase Intention Di E-Commerce Lazada - Poppy Avianti; Siti Aminah (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The rapid development of the internet has the potential to become a new business tool for profit, which is then used by business people to carry out business activities using electronic trading systems or often called e-commerce in meeting the needs of society more efficiently and effectively. This study aims to determine the effect of Electronic Word Of Mouth and Brand Image on Purchase Intention in E-commerce Lazada. This research was conducted on 84 respondents who are active students of the Faculty of Economics and Business Class of 2019 UPN â€œVeteranâ€ Jawa Timur who knew Lazada e-commerce. And selected using non-probability sampling and purposive sampling methods. The data analysis technique in this study is the Partial Least Square (PLS) analysis technique. Data is primary data by using the method of collection through a questionnaire. The Likert scale is used to measure variables in this study. The results of the study show that Electronic Word Of Mouth and Brand Image have a significant positive effect on Purchase Intention. Keywords : Brand Image; E-commerce; Electronic Word Of Mouth; Purchase Intentions Abstrak Perkembangan internet yang pesat berpotensi sebagai sarana bisnis baru untuk memperoleh keuntungan, yang kemudian dijadikan para pebisnis untuk melakukan aktivitas bisnis dengan menggunakan sistem perdagangan elektronik atau sering disebut ecommerce dalam memenuhi kebutuhan masyarakat yang lebih efisien dan efektif. Penelitian ini bertujuan untuk mengetahui pengaruh Electronic Word Of Mouth dan Brand Image terhadap Purchase Intention di Ecommerce Lazada. Penelitian ini dilakukan terhadap 84 responden yang merupakan mahasiswa/mahasiswi aktif Fakultas Ekonomi dan Bisnis Angkatan 2019 UPN Veteran Jawa Timur yang mengetahui e-commerce Lazada. Dan dipilih menggunakan metode non-probability sampling dan purposive sampling. Teknik analisis data pada penelitian adalah teknik analisis Partial Least Square (PLS). Data merupakan data primer dengan menggunakan metode pengumpulan melalui kuesioner. Skala likert digunakan untuk mengukur variabel pada penelitian ini. Hasil dari penelitian menunjukkan bahwa Electronic Word Of Mouth dan Brand Image berpengaruh siginifikan positif terhadap Purchase Intention. Kata Kunci: Brand Image; E-commerce; Electronic Word Of Mouth; Purchase Intention